Goal-setting and volitional behavioural change: Results from a school meals intervention with vitamin-A biofortified sweetpotato in Nigeria - Lagerkvist, Carl Johan; Okello, J.J.; Adekambi, S.; Kwikiriza, N.; Abidin, P.E.; Carey, E.E. (Elsevier, 2018)
Malnutrition, particularly vitamin A deficiency, is a major public health problem in many developing countries. This study investigated whether priming or self-generation of goals, or whether attention to instrumental or experiential goals together with use of a reminder condition or not, promotes dietary behaviour intentions and change. A set of 556 randomly selected children aged 7–12 in Osun state, Nigeria, participated in an four-week intervention and field experiment in which a meal based on orange-fleshed sweetpotato, rich in pro-vitamin A, was introduced on five occasions as a complement to the existing school meal. Baseline intentions, anticipated feelings and repeated measures of post-consumption and experience were assessed. The analyses included a generalised linear mixed model for consumption and a linear mixed model for feelings and experience. The results confirmed that attention to instrumental goals undermines goal pursuit, while a focus on experiential goals increases the persistence of pursuit. Priming of experiential goals should be recommended, especially because this approach evokes positive feelings after eating. There was no evidence of an effect from repeated pairing of goals with the school meal, but use of planning by stating intentions increased the amount eaten. These results have implications for how school meals programmes should be designed to better align personal motivation with behavioural change in relation to dietary health.